“Ca. Nitrosocosmicus” members are the dominant archaea associated with plant rhizospheres - Ui-Ju Lee; Joo-Han Gwak; Seungyeon Choi; Man-Young Jung; Tae Kwon Lee; Hojin Ryu; Samuel Imisi Awala; Wolfgang Wanek; Michael Wagner; Zhe-Xue Quan; Sung-Keun Rhee (mSphere)
ABSTRACT Archaea catalyzing the first step of nitrification in the rhizosphere possibly have an influence on plant growth and development. In this study, we found a distinct archaeal community, dominated by ammonia-oxidizing archaea (AOA), associated with the root system of pepper (Capsicum anuum L.) and ginseng plants (Panax ginseng C.A. Mey.) compared to bulk soil not penetrated by roots. While the abundance of total AOA decreased in the rhizosphere soils, AOA related to “Candidatus Nitrosocosmicus,” which harbor gene encoding manganese catalase (MnKat) in contrast to most other AOA, dominated the AOA community in the rhizosphere soils. For both plant species, the ratio of copy numbers of the AOA MnKat gene to the amoA gene (encoding the ammonia monooxygenase subunit A) was significantly higher in the rhizospheres than in bulk soils. In contrast to MnKat-negative strains from other AOA clades, the catalase activity of a representative isolate of “Ca. Nitrosocosmicus” was demonstrated. Members of this clade were enriched in H2O2-amended bulk soils, and constitutive expression of their MnKat gene was observed in both bulk and rhizosphere soils. Due to their abundance, “Ca. Nitrosocosmicus” members can be considered important players mediating the nitrification process in rhizospheres. The dominance of this MnKat-containing AOA in rhizospheres of agriculturally important plants hints at a previously overlooked AOA-plant interaction.IMPORTANCEAmmonia-oxidizing archaea (AOA) are widespread in terrestrial environments and outnumber other ammonia oxidizers in the rhizosphere, possibly exerting an influence on plant growth and development. However, little is known about the selection forces that shape their composition, functions, survival, and proliferation strategies in the rhizosphere. Here, we observed a distinct AOA community on root systems of two different plant species compared to bulk soil. Our results show that the “Ca. Nitrosocosmicus” clade, which possesses functional MnKat genes unlike most other AOA, dominated the rhizosphere soils. Moreover, members of this clade were enriched in H2O2-amended bulk soil, which mimics the ROS stress in root systems. While research on AOA-plant interactions in the rhizosphere is still in its infancy, these findings suggest that “Ca. Nitrosocosmicus” may be an important clade of AOA with potential AOA-plant interaction.